2016
DOI: 10.1371/journal.pone.0166367
|View full text |Cite
|
Sign up to set email alerts
|

Non-Communicable Disease Clinical Practice Guidelines in Brazil: A Systematic Assessment of Methodological Quality and Transparency

Abstract: BackgroundAnnually, non-communicable diseases (NCDs) kill 38 million people worldwide, with low and middle-income countries accounting for three-quarters of these deaths. High-quality clinical practice guidelines (CPGs) are fundamental to improving NCD management. The present study evaluated the methodological rigor and transparency of Brazilian CPGs that recommend pharmacological treatment for the most prevalent NCDs.MethodsWe conducted a systematic search for CPGs of the following NCDs: asthma, atrial fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
24

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 51 publications
3
35
0
24
Order By: Relevance
“…This study is a complementary analysis of a systematic review and assessment of the methodological quality and transparency of the Brazilian CPGs 14 . This systematic review was registered in PROSPERO.…”
Section: Methods Study Designmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is a complementary analysis of a systematic review and assessment of the methodological quality and transparency of the Brazilian CPGs 14 . This systematic review was registered in PROSPERO.…”
Section: Methods Study Designmentioning
confidence: 99%
“…As previously described 14 , 661 studies were found in the systematic search, of which 26 met the eligibility criteria and were assessed for meth-odological quality and transparency. Details on the studies that were included, excluded, and on the PRISMA checklist can be found in a previously published study 14 .…”
Section: Methods Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…de Molino et al 2016 21. (*) Foi observado significância estatística para "rigor do desenvolvimento" (p = 0,03) e "clareza e apresentação (p = 0,01)".5.3.4.…”
unclassified